1998
DOI: 10.1063/1.366927
|View full text |Cite
|
Sign up to set email alerts
|

Boron diffusion across silicon–silicon germanium boundaries

Abstract: Most boron diffusion studies in Si–Ge have been made in regions of uniform germanium content. In this paper diffusion is observed from a boron-doped epitaxial silicon layer across surrounding Si–Ge layers. Pileup of boron in the Si–Ge layers shows that the activity coefficient for boron in Si–Ge is lower than that for pure silicon. A simple pairing model for Si–B interaction fitted the pileup quite well, with the same equilibrium constant applying to both Si0.9Ge0.1 and Si0.97Ge0.03 layers. The effect of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(31 citation statements)
references
References 20 publications
2
27
0
2
Order By: Relevance
“…Hitherto, it has been proposed that boron diffusion could be retarded in compressive strained Si 1-x Ge x alloys [8]- [12]. Boron diffusivity in strained as well as relaxed Si 1-x Ge x alloys largely decreased at Ge content up to 40% but increased again at high Ge levels were also reported [13]- [15]. Bang et al showed the boron diffusion reduced in Si 1-x Ge x alloy by DFT calculation and they pointed out that the retarded B diffusion could be attributed to the following reasons: 1) the presence of Ge increases the migration energy of a Si self-interstitial defect then reduces the numbers of Si self-interstitials available for B diffusion; and 2) increases the migration energy of the B interstitial [16].…”
Section: Introductionmentioning
confidence: 89%
“…Hitherto, it has been proposed that boron diffusion could be retarded in compressive strained Si 1-x Ge x alloys [8]- [12]. Boron diffusivity in strained as well as relaxed Si 1-x Ge x alloys largely decreased at Ge content up to 40% but increased again at high Ge levels were also reported [13]- [15]. Bang et al showed the boron diffusion reduced in Si 1-x Ge x alloy by DFT calculation and they pointed out that the retarded B diffusion could be attributed to the following reasons: 1) the presence of Ge increases the migration energy of a Si self-interstitial defect then reduces the numbers of Si self-interstitials available for B diffusion; and 2) increases the migration energy of the B interstitial [16].…”
Section: Introductionmentioning
confidence: 89%
“…When annealing at a furnace temperatures of 750 1C, boron diffusion decreases with increasing Ge content [9] presenting preferential Ge-B bonding as reasoning for retardation of B diffusion in SiGe [9][10][11]. Point defect injection from annealing ambient experiments in Si-rich SiGe suggests that B diffusion remains interstitially mediated [12,13] with fractional interstitialcy constants comparable to that of pure Si [14].…”
Section: Introductionmentioning
confidence: 99%
“…Boron diffusivity under this circumstance has been modeled in [3,4] with a diffusivity retardation that is an exponential function of the strain. Alternatively, it is claimed that the retardation is from Ge-B pairing instead [5,6]. A quantitative assessment of the respective contribution from mechanical strain and Ge doping is therefore necessary for accurate boron modeling in SiGe.…”
Section: Introductionmentioning
confidence: 99%